Optimization of the South Coast Seawater Purification Process by Using a Circulating Adsorption Column - Amallia Ferhat; Mohammad Prasanto Bimantio (OPSI, 2022)
Seawater which contains salt, metal components and mycobacteria is part of Indonesia's natural resources. Behind its abundance, not many benefits can be used, such as clean water to drinking water. Therefore, various technologies are needed to reduce the salt content and other components. In this study, a portable seawater purifier based on the adsorption function was used. The purification apparatus is in the form of a column, and has a series of plates that are placed as a support for the filling material in order to increase residence time and complete the purification process. Materials used as adsorbents in this study include ceramic biological balls, ammonite, volcanic rock, activated carbon and zeolite. Each material is organized in a filter bag for easy installation and cleaning. The equipment construction is arranged where in addition to the column there is also a circulation flow system for seawater to ensure the purification process can run optimally. The circulation process uses a buffer tank and a booster pump back to the column input line. The variable in this study, namely the location of the water sample at Ngobaran Beach, Gunungkidul. Another variable is the filtration rate. Based on the pH value of the TDS analysis and the adsorption results of seawater samples, it can be seen that the 2-stage adsorption process is the most optimal process configuration compared to other levels. This is because the 2-stage adsorption process obtained the smallest TDS value and the most suitable pH value for clean water. The results of this study can be an alternative for an easy and portable seawater purification method. This research can continue to be developed with innovations from the type of filling material and the configuration of the adsorption column used.